Acceleration of bone formation during fracture healing by injectable collagen powder and human basic fibroblast growth factor containing a collagen‐binding domain from Clostridium histolyticum collagenase. Issue 9 (9th October 2013) - Saito, Wataru; Uchida, Kentaro; Ueno, Masaki; Matsushita, Osamu; Inoue, Gen; Nishi, Nozomu; Ogura, Takayuki; Hattori, Shunji; Fujimaki, Hisako; Tanaka, Keisuke; Takaso, Masashi
Abstract Growth factor delivered with implantable biomaterials has been used to both accelerate and ensure healing of open fractures in human patients. However, a major limitation of implantable biomaterials is the requirement for open surgical placement. Here, we developed an injectable collagen material‐based bone formation system consisting of injectable collagen powder with fibril morphology and collagen triple helix conformation, and basic fibroblast growth factor (bFGF) fused to the collagen‐binding domain (CBD) of Clostridium histolyticum collagenase. The affinity of the CBD towards collagen was confirmed by the results of collagen‐binding assays. Moreover, the combination of the collagen binding‐bFGF fusion protein (CB‐bFGF) with injectable collagen powder induced bone formation at protein concentrations lower than those required for bFGF alone in mice fracture models. Taken together, these properties suggest that the CB‐bFGF/collagen powder composite is a promising injectable material for bone repair in the clinical setting. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3049–3055, 2014.